The aesthetics of atmospheres - Böhme, Gernot, 1937-2022 (Ambiances, atmospheres and sensory experiences of spaces, 2017)
Interest in sensory atmospheres and architectural and urban ambiances has been growing for over 30 years. A key figure in this field is acclaimed German philosopher Gernot B hme whose influential conception of what atmospheres are and how they function has been only partially available to the English-speaking public. This translation of key essays along with an original introduction charts the development of Gernot B hme's philosophy of atmospheres and how it can be applied in various contexts such as scenography, commodity aesthetics, advertising, architecture, design, and art. The phenomenological analysis of atmospheres has proved very fruitful and its most important, and successful, application has been within aesthetics. The material background of this success may be seen in the ubiquitous aestheticization of our lifeworld, or from another perspective, of the staging of everything, every event and performance. The theory of atmospheres becoming an aesthetic theory thus reveals the theatrical, not to say manipulative, character of politics, commerce, of the event-society. But, taken as a positive theory of certain phenomena, it offers new perspectives on architecture, design, and art. It made the spatial and the experience of space and places a central subject and hence rehabilitated the ephemeral in the arts. Taking its numerous impacts in many fields together, it initiated a new humanism: the individual as a living person and his or her perspective are taken seriously, and this fosters the ongoing democratization of culture, in particular the possibility for everybody to participate in art and its works.